Defective autophagy contributes to endometrial epithelial-mesenchymal transition in intrauterine adhesions - Zhenhua Zhou; Huiyan Wang; Xiwen Zhang; Minmin Song; Simin Yao; Peipei Jiang; Dan Liu; Zhiyin Wang; Haining Lv; Ruotian Li; Ying Hong; Jianwu Dai; et al. (Taylor & Francis, 2022)
Intrauterine adhesions (IUA), characterized by endometrial fibrosis, is a common cause of uterine infertility. We previously demonstrated that partial epithelial-mesenchymal transition (EMT) and the loss of epithelial homeostasis play a vital role in the development of endometrial fibrosis. As a pro-survival strategy in maintaining cell and tissue homeostasis, macroautophagy/autophagy, conversely, may participate in this process. However, the role of autophagy in endometrial fibrosis remains unknown. Here, we demonstrated that autophagy is defective in endometria of IUA patients, which aggravates EMT and endometrial fibrosis, and defective autophagy is related to DIO2 (iodothyronine deiodinase 2) downregulation. In endometrial epithelial cells (EECs), pharmacological inhibition of autophagy by chloroquine (CQ) promoted EEC-EMT, whereas enhanced autophagy by rapamycin extenuated this process. Mechanistically, silencing DIO2 in EECs blocked autophagic flux and promoted EMT via the MAPK/ERK-MTOR pathway. Inversely, overexpression of DIO2 or triiodothyronine (T3) treatment could restore autophagy and partly reverse EEC-EMT. Furthermore, in an IUA-like mouse model, the autophagy in endometrium was defective accompanied by EEC-EMT, and CQ could inhibit autophagy and aggravate endometrial fibrosis, whereas rapamycin or T3 treatment could improve the autophagic levels and blunt endometrial fibrosis. Together, we demonstrated that defective autophagy played an important role in EEC-EMT in IUA via the DIO2-MAPK/ERK-MTOR pathway, which provided a potential target for therapeutic implications.
Abbreviations: ACTA2/α-SMA: actin alpha 2, smooth muscle; AMPK: adenosine 5’-monophosphate-activated protein kinase; AKT/protein kinase B: AKT serine/threonine kinase; ATG: autophagy related; CDH1/E-cadherin: cadherin 1; CDH2/N-cadherin: cadherin 2; CQ: chloroquine; CTSD: cathepsin D; DIO2: iodothyronine deiodinase 2; DEGs: differentially expressed genes; EECs: endometrial epithelial cells; EMT: epithelial-mesenchymal transition; FN1: fibronectin 1; IUA: intrauterine adhesions; LAMP1: lysosomal associated membrane protein 1; LPS: lipopolysaccharide; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MAPK: mitogen-activated protein kinase; MTOR: mechanistic target of rapamycin kinase; Rapa: rapamycin; SQSTM1/p62: sequestosome 1; T3: triiodothyronine; T4: tetraiodothyronine; TFEB: transcription factor EB; PBS: phosphate-buffered saline; TEM: transmission electron microscopy; TGFB/TGFβ: transforming growth factor beta.
Keywords: Biochemistry; Medicine; Cell Biology; Genetics; Chemical Sciences not elsewhere classified; Immunology; Biological Sciences not elsewhere classified; Mathematical Sciences not elsewhere classified; Developmental Biology